2009
DOI: 10.1186/1471-2474-10-47
|View full text |Cite
|
Sign up to set email alerts
|

Strength characterization of knee flexor and extensor muscles in Prader-Willi and obese patients

Abstract: Background: despite evidence of an obesity-related disability, there is a lack of objective muscle functional data in overweight subjects. Only few studies provide instrumental strength measurements in non-syndromal obesity, whereas no data about Prader-Willi syndrome (PWS) are reported. The aim of our study was to characterize the lower limb muscle function of patients affected by PWS as compared to non-syndromal obesity and normal-weight subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
5
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 37 publications
5
63
5
2
Order By: Relevance
“…Individuals who are obese exhibit altered lower limb strength compared with healthy weight individuals 1418. Lower limb strength can be characterized in terms of absolute strength and relative strength.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who are obese exhibit altered lower limb strength compared with healthy weight individuals 1418. Lower limb strength can be characterized in terms of absolute strength and relative strength.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the higher absolute muscle strength of obese individuals could be more relevant for larger muscle groups involved in lifting and/or moving the body (i.e., knee and trunk extensors). Whilst some studies found higher absolute isokinetic/isometric strength of knee/trunk extensors in obese subjects [7,9], others have reported no significant difference in maximal isokinetic torque of knee/elbow flexors between obese and nonobese people [7,9,15]. Thus, the extra-load associated with severe The reference angle for isometric measurements was taken as 0°= full extension Isokinetic torque was measured in all studies as the peak torque produced during the concentric action obesity could act as a chronic training stimulus generating favorable muscle adaptations.…”
Section: Impact Of Obesity On Muscle Strengthmentioning
confidence: 99%
“…Comparando-se o pico de toque em pacientes de diferentes idades, observou-se que os valores da força para os extensores do joelho eram, na média geral, a metade do valor encontrado para os extensores. (CAPODAGLIO; PAOLO et al, 2008).…”
Section: Discussão Dos Resultadosunclassified